A Quantum Leap in Energy Efficiency to Put the Sustainable Development Goals in Closer Reach. Issue 3 (30th May 2018) - Puig, Daniel; Farrell, Timothy Clifford; Moner‐Girona, Magda
Abstract: Targeted improvements in the way energy is transformed, distributed and used can accelerate progress toward achieving the United Nations' Sustainable Development Goals (SDGs). Compared to a situation in which no indicators are defined and monitored, tracking progress through indicators would make it easier to reap the full developmental benefits associated with improvements in energy efficiency. We call upon G20 leaders to adopt SDG‐specific energy‐efficiency indicators, with a view to ultimately accelerating progress toward achieving the United Nations' Sustainable Development Goals. Abstract : We call upon G20 leaders to adopt SDG‐specific energy‐efficiency indicators, with a view to ultimately accelerating progress toward achieving the United Nations' Sustainable Development Goals.